Design of N-graphene-NbOx hybrid nanosheets with sandwich-like structure and electrocatalytic performance towards oxygen reduction reaction. (10th March 2015) - Wu, Q.; Liao, L.; Zhang, Q.; Nie, Y.; Xiao, J.; Wang, S.; Dai, S.; Gao, Q.; Zhang, Y.; Sun, X.; Liu, B.; Tang, Y.
Graphical abstract: Highlights: An intercalation- in situ carbonization strategy is reported for multilayer material. The obtained multilayer hybrid material exhibits enhanced ORR performance. It is confirmed that the oxygen vacancy and synergetic coupling effect are crucial. Abstract: Advanced materials for electrocatalytic oxygen reduction reaction (ORR) is crucial to a number of renewable energy applications. Herein, a hybrid of nitrogen-doped graphene (N-graphene) and NbOx (x = 2∼2.5) semiconductor nanosheets with sandwich-like structure has been designed and synthesized via a strategy of intercalation-in situ carbonization. The obtained multilayer hybrid material exhibits quite positive onset potential of ORR, good stability and excellent selectivity for ORR with high methanol tolerance. The enhanced performance could be attributed to the active oxygen vacancy from the partial reduction of Nb (V) during the carbonization process and the synergetic coupling effect resulting from the molecular level contact of N-graphene and NbOx (x = 2∼2.5) nanosheets, which makes it a promising substitute of platinum-based materials for renewable energy applications.